Safety and immunogenicity of Fc‐EDA, a recombinant ectodysplasin A1 replacement protein, in human subjects - Körber, Iris; Klein, Ophir D.; Morhart, Patrick; Faschingbauer, Florian; Grange, Dorothy K.; Clarke, Angus; Bodemer, Christine; Maitz, Silvia; Huttner, Kenneth; Kirby, Neil; Durand, Caroline; Schneider, Holm (British journal of clinical pharmacology, 2020)
In X‐linked hypohidrotic ectodermal dysplasia, the most frequent ectodermal dysplasia, an inherited deficiency of the signalling protein ectodysplasin A1 (EDA1) impairs the development of the skin and its appendages, various eccrine glands, and dentition. The severe hypohidrosis common to X‐linked hypohidrotic ectodermal dysplasia patients may lead to life‐threatening hyperthermia, especially during hot weather or febrile illness. Fc‐EDA, an EDA1 replacement protein known to prevent the disease in newborn animals, was tested in 2 clinical trials (human adults and neonates) and additionally administered under compassionate use to 3 infants in utero. The data support the safety of Fc‐EDA and efficacy if applied prenatally. Anti‐drug antibodies were detected after intravenous administration in adult males and nonpregnant females, but not in pregnant women when Fc‐EDA was delivered intra‐amniotically. Most importantly, there was no detectable immune response to the investigational drug in neonates treated by intravenous infusions and in infants who had received Fc‐EDA in utero. In conclusion, the safety profile of this drug encourages further development of prenatal EDA1 replacement therapy.